Study on plastic recycling in Petaling Jaya / Zhila Hemati - Hemati, Zhila (2012)

(untitled)
Recycling is an option in waste management that basically helps in the reduction of solid waste generation. While some materials cannot be reused or recycled, plastic is a material that has been more frequently recycled in the last two decades. This study was aimed at characterizing municipal solid waste (MSW) in Petaling Jaya (PJ), Malaysia. It also investigated the degree of residents‘ plastic recycling awareness in relation to identifying the problems affecting plastic recycling. An outlined questionnaire was designed and distributed to residents in the study area. The research includes data collection through field survey; sampling, segregation and wet weight measurement of the wastes and distribution of questionnaires. Analysis of data for waste compensation and questionnaires were carried out using Microsoft Excel and the Statistical Package for Social Sciences (SPSS) software. Plastic component was approximately 21% of the waste stream in PJ, though organic component formed the bulk portion (42%). Although about 67% of PJ residents knew the meaning of recycling, only 22% of the respondents practiced it. About 60% of plastic waste in PJ is still being disposed off into landfill. This finding indicated that residents are not aware of 3Rs (Recycling, Reuse, and Reduce). This might be attributed to lack of facilities and suitable training methods on plastic recycling. In PJ area, 31% of the respondents showed their dissatisfaction over insufficient recycling bins provided for plastic waste separation at source. The citizens from PJ felt that inadequate knowledge on recycling and ignorance are the major setbacks for citizens‘ non-cooperation over plastic recycling. The concentration of plastics obtained in the waste stream is high. However, the research identified a number of problems that hinder efficient recycling of plastic is PJ. Such problems ranged from lack of awareness (39%), level of literacy (36%) v to unavailability of recycling facilities (31%). For a more progressive citizens‘ involvement in plastic recycling in PJ, government and waste management authorities should play a key role in providing the basic infrastructures.